Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1953
DOI: 10.2172/915417
|View full text |Cite
|
Sign up to set email alerts
|

The Path of Carbon in Photosynthesis. XXI. The Cyclic Regenerationof Carbon Dioxide Acceptor

Abstract: Photosynthesizing plants have been exposed t o C O2 f o r short periods of the(0.4 t o 15 sec,) and the products of carbon dioxide reduction analyzed by paper chramatography and radioaut ography .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
92
0
5

Year Published

1957
1957
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(98 citation statements)
references
References 0 publications
1
92
0
5
Order By: Relevance
“…The process of carbon assimilation via the Calvin -Benson -Bassham cycle [1] requires initial fixation of CO 2 by the enzyme ribulose-1,5-bisphosphate carboxylase/oxygenase (RuBisCO) to form the three-carbon molecule 3-phosphoglycerate (3-PGA). RuBisCO is thought to have evolved in bacteria under anoxic conditions approximately 3.5 billion years ago [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…The process of carbon assimilation via the Calvin -Benson -Bassham cycle [1] requires initial fixation of CO 2 by the enzyme ribulose-1,5-bisphosphate carboxylase/oxygenase (RuBisCO) to form the three-carbon molecule 3-phosphoglycerate (3-PGA). RuBisCO is thought to have evolved in bacteria under anoxic conditions approximately 3.5 billion years ago [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…This reaction has been found to occur in intact algae (2) and in cell-free preparations of several organisms (11,12,16). The reaction occurs with a large loss in free energy (2,16), and in this aspect differs from most biological carboxylations. Under certain conditions, this property would have a selective advantage as a reaction to be retained where any type of C02 fixation were occurring.…”
mentioning
confidence: 97%
“…In addition to working Manuscript received February 9, 1959. 2 Research carried out at Brookhaveni National Laboratory under the auspices of the U. S. Atomic Energy Commission and in part supported by a grant from the National Science Foundation to one of us (M.G.). ' Abbreviations used in this paper: PGA for 3-phosphoglyceric acid; TPN for triphosphopyridine nucleotide; DPN for diphosphopyridine nucleotide; G-3-P for Dglyceraldehyde-3-phosphate; RuDP for ribulose 1,5-diphosphate.…”
mentioning
confidence: 99%
“…In addition, it has been reported that the interconversion of glycine and serine does not occur in plant extracts without the addition of tetrahvdrofolic acid (21). The most likely precursor for the uniformly labeled glycine is glycolate, whichl is uniformiily labeled during photosynthesis (2). The tiniformly labeled glycine may be produced by residual cytoplasmic enzymes absorbed to the unwashed chloroplasts.…”
mentioning
confidence: 99%